2017
DOI: 10.4172/2167-0897.1000259
|View full text |Cite
|
Sign up to set email alerts
|

What is the Significance of Leftward Cradling Bias?

Abstract: Maternal cradling bias is the act of human females to tend to cradle new-borns to the left side in the first few weeks of life. Many factors contributing to the occurrence of leftward cradling bias have been explored including handedness and hemispheric dominance, neural development in neonates, breast feeding influences and early communicative. Accepted best practices for developmental support for premature infants incorporate positioning and holding neonates in their protocols. Questions as to what function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…in this study attended a Central London primary school, which drew from a diverse multicultural catchment area. Moreover, the findings are consistent with previous research across a range of schools and ages (see Jones, 2017). Findings from the present study demonstrated a population-level LCB, supporting an early evolutionary propensity for population-level left visual field and right hemisphere dominance for social-emotional processing (Bourne & Todd, 2004).…”
Section: Cradling Side and Hand Dominancesupporting
confidence: 92%
“…in this study attended a Central London primary school, which drew from a diverse multicultural catchment area. Moreover, the findings are consistent with previous research across a range of schools and ages (see Jones, 2017). Findings from the present study demonstrated a population-level LCB, supporting an early evolutionary propensity for population-level left visual field and right hemisphere dominance for social-emotional processing (Bourne & Todd, 2004).…”
Section: Cradling Side and Hand Dominancesupporting
confidence: 92%